VD_FINDINFO Arrêt / 2023 / 23 vom 12. Juli 2023 - VD Tribunal cantonal (2023)
ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, DEGRÉ DE L'INVALIDITÉ, RÉVISIONPRESTATION D'ASSURANCE | 16 LPGA, 17 LPGA, 6 LPGA, 7 LPGA, 8 al. 1 LPGA, 88a al. 1 RAI